Improving the diagnosis of acute pyelonephritis using Doppler ultrasound (Texas Journal of Medical Science, 2022)
This article describes the way of improving the diagnosis of cute pyelonephritis, which is a bacterial infection of the renal pelvis and parenchyma most commonly seen in young women. It remains common and continues to have significant morbidity in certain groups of patients, using doppleroghraphy